Gold-Immobilized Photonic Crystal Fiber-Based SPR Biosensor for Detection of Malaria Disease in Human Body - Chaudhary, Vijay Shanker; Kumar, Dharmendra; Kumar, Santosh (IEEE sensors journal, 2021)
This article presents the photonic crystal fiber (PCF) based surface plasmon resonance (SPR) biosensor for early detection of malaria disease in humans by measurement of the variation of red blood cells (RBCs). In the proposed PCF, two layers of air holes are arranged in a hexagonal lattice structure and a thin film of gold-coating is used over PCF for the occurrence of SPR phenomena. It occurs when surface plasmon polariton (SPP)-mode coupled with the core-mode during phase-matching conditions. Malaria infected RBCs samples are filled into the PCF, which have own refractive index (RI) that shift the SPR resonance wavelength during confinement loss measurement. The resonance wavelength of malaria-infected RBCs samples is different from their normal RBCs samples due to the difference in RI of infected and normal RBCs samples. The proposed work is helpful in the detection of different stages of malaria-infected RBCs such as ring phase, trophozoite phase and Schizont phase by measuring the shift in resonance wavelength. The calculated wavelength sensitivities of the proposed sensor for the ring phase, trophozoite phase and Schizont phase RBCs are 13714.29 nm/RIU, 9789.47 nm/RIU, and 8068.97 nm/RIU, respectively in x-polarized direction and 14285.71 nm/RIU, 10000 nm/RIU, and 8206.9 nm/RIU, respectively in y-polarized direction with the maximum detection limit of 0.029. The proposed PCF-based SPR biosensor is suitable for the early diagnosis of malaria disease due to its enhanced sensing performance (low detection limit and high sensitivity).